RANCANG BANGUN ANIMASI 3 DIMENSI SEBAGAI MEDIA PEMBELAJARAN PADA MATA PELAJARAN MENGINSTALASI PC - Febri Yuningsih; Ahmaddul Hadi; Asrul Huda (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
One of the success of an organization of educators in implementing the learning is how educators attempt to deliver the message , and information theory to the students to understand the lessons and information more quickly and make the lessons more interesting and easier to understand, then educators need to create an exciting learning media such as media learning 3D animation ( three- dimensional ) . The purpose of this thesis is to design and build 3D animated instructional media on subjects Installing PC on Skills Program Computer Engineering and Networks . 3D animation creation using real-time , with the Pre-Production stages that include a search of ideas and materials will be made in 3D animation , character design , script, and storyboard creation , later stages of production , including the manufacture of modeling a design object / character , the next stage is the stage of post- production is a compilation of Final Editing and pengecekkan element if an error occurs then the process is repeated . Afterwards, proceed to the next stage of the rendering which will output the video as a whole . In the process of making 3D animsi using Blender 3D application version 2.6.5 . This final project will result in a medium of learning in subjects install the PC in the Program of Computer Engineering and Networks. Keywords        : learning process , instructional media , 3D animation